Real-time high contrast vein visualisation in active dynamic thermography - Lim, Jia Ler (Nanyang Technological University, 2020)
Vein Visualization Technology has become increasingly ubiquitous as the benefits of such applications become more apparent. By using a cooling means that is configured to cool the target area of the subject body; hence, effecting a thermal change to the target area upon removal of cooling. Coupled with an infrared thermal sensor to capture a series of transient thermal images of the target area. This project would like to use a novel method of extracting dynamic synthetic thermal images, over the time of the thermal image acquisition, while ensuring a high contrast image for an efficient vein visualization. While working towards utilizing active dynamic thermography (ADT)-based real-time vein projection system, which involves mapping of the temperature over the target area, upon external stimulation, and a simultaneous projection of synthetic images. The project aims to investigate a real-time projection system using ADT, given the fact that in addition to vein visualization, such a device can be used for other medical diagnosis and monitoring applications, hence there is huge market potential. This project will also study the effects on the contrast of the dynamic synthetic images obtained with different cooling temperatures (5°C, 8°C, 11°C) used.